1999
DOI: 10.1162/089892999563689
|View full text |Cite
|
Sign up to set email alerts
|

Differential Contributions of the Left and Right Inferior Parietal Lobules to Number Processing

Abstract: We measured cerebral activation with functional magnetic resonance imaging at 3 Tesla while eight healthy volunteers performed various number processing tasks known to be dissociable in brain-lesioned patients: naming, comparing, multiplying, or subtracting single digits. The results revealed the activation of a circuit comprising bilateral intraparietal, prefrontal, and anterior cingulate components. The extension and lateralization of this circuit was modulated by task demands. The intraparietal and prefront… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

50
374
4
17

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 524 publications
(445 citation statements)
references
References 49 publications
50
374
4
17
Order By: Relevance
“…The bilateral inferior parietal area is considered an important region for quantity processing and is independent of input-output channels and tasks (e.g., Chochon, Cohen, van de Moortele, & Dehaene, 1999). In addition, we also found that numbers and dot arrays had greater activation in the prefrontal cortex than did numeral classifiers and tool nouns.…”
Section: Discussionsupporting
confidence: 59%
“…The bilateral inferior parietal area is considered an important region for quantity processing and is independent of input-output channels and tasks (e.g., Chochon, Cohen, van de Moortele, & Dehaene, 1999). In addition, we also found that numbers and dot arrays had greater activation in the prefrontal cortex than did numeral classifiers and tool nouns.…”
Section: Discussionsupporting
confidence: 59%
“…This idea has been supported by some studies (e.g., Chochon et al, 1999;Dehaene et al, 1999;Lee, 2000;Simon et al, 2002), but not others (e.g., Andres et al, 2011;Dehaene et al, 1996;Delazer and Benke, 1997;Pesenti et al, 2000;Tucha et al, 1997;Van Harskamp et al, 2002;Zhou et al, 2007). For example, several studies have found that injuries to the angular gyrus or even the removal of this brain region did not affect subjects' performance on multiplication (e.g., Delazer and Benke, 1997;Tucha et al, 1997;van Harskamp et al, 2002).…”
Section: Geom > Tool Conjunctionmentioning
confidence: 97%
“…The cortical areas in patients with brain injury that have been studied by neural-imaging and the results accepted in the literature have shown that areas of the parietal lobe with involvement of the temporal areas and intraparietal sulcus, can be more susceptible to cause isolated mathematical changes 12,13 . however, broad cortical injuries that also involve regions proximal to the left temporal cortex, left and right parietal and frontal lobe, are susceptible to conduct concomitant language disorders and numerical and calculating processing [13][14][15][16] .…”
mentioning
confidence: 99%
“…however, broad cortical injuries that also involve regions proximal to the left temporal cortex, left and right parietal and frontal lobe, are susceptible to conduct concomitant language disorders and numerical and calculating processing [13][14][15][16] .…”
mentioning
confidence: 99%